Utilization of Tiktok Application as Da’wah Media and Innovation in Conveying Islamic Values in the Digital Age - Aldi, Muhammad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This research aims to analyze how the TikTok application can be used as an innovative da'wah medium in conveying Islamic values in the digital era. The main focus of this research is to explore the role of Islamic-based creative content in increasing public understanding and participation in religious teachings, especially among the younger generation. This study used a qualitative approach with a content analysis method on a number of da'wah videos on TikTok that were purposively selected based on the popularity and relevance of the message. Additional data was obtained through in-depth interviews with Islamic content creators and analysis of user comments to understand audience responses. The results show that TikTok has great potential as a medium for da'wah through short video formats that are creative, interesting, and easily accessible. Islamic values-based content, such as inspirational stories, understanding of Qur'anic verses, and explanation of hadith, can be presented in a short but effective manner. Content creators who are able to combine Islamic values with digital trends have succeeded in attracting the attention of young audiences, increasing religious awareness, and building positive discussions. The implication of this research shows that the use of TikTok as a medium for da'wah opens up new opportunities in delivering Islamic messages widely and relevantly in the digital era. The contribution of this research is to provide insights for preachers and religious institutions to utilize digital platforms effectively, and encourage innovation in modern technology-based da'wah strategies. This research also underscores the importance of digital literacy for Islamic content creators in order to deliver messages that are in accordance with religious and ethical values. Keywords: Tiktok, Innovation, Islamic Values, Digital